Cyclic homodimer formation by singlet oxygen-mediated oxidation of carnosine - Kawakami, Hiroko; Itakura, Yuki; Yamamoto, Tetsuya; Yoshiya, Taku (Frontiers in Chemistry, 2024)
Although carnosine (β-Ala-L-His) is one of physiological protectants against in vivo damages caused by reactive oxygen species (ROS), its reactivity against singlet oxygen (1O2), an ROS, is still unclear at the molecular level. Theoretically, the reaction consists of two steps: i) oxygenation of the His side chain to form an electrophilic endoperoxide and ii) nucleophilic addition to the endoperoxide. In this study, the end product of 1O2-mediated carnosine oxidation was evaluated using 2D-NMR and other analytical methods both in the presence and absence of external nucleophiles. Interestingly, as the end product without external nucleophile, a cyclic homodimer was confirmed under our particular conditions. The reaction was also replicated in pork specimens.